2018
DOI: 10.18203/issn.2454-5929.ijohns20180703
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of superiorly based circumferential tympanomeatal flap tympanoplasty with anteriorly anchoring flap tympanoplasty in large, subtotal, and anterior tympanic membrane central perforations in chronic suppurative otitis media of mucosal type

Abstract: Underlay technique is widely used and relatively simple to perform as the graft is placed entirely medial to the ABSTRACT Background: The main objective of the study was to assess and compare the graft uptake, hearing improvement, complications in large, subtotal, and anterior moderate perforations by each technique viz; superiorly based circumferential tympanomeatal flap tympanoplasty (STT)/full cuff and anterior anchoring flap tympanoplasty (AAT)/anterior tucking. Methods: In our study of 30 cases age group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
1
0
1
Order By: Relevance
“…Yoon et al had all the patients aged 15 years or less [9]. In contrast to this study, Rathi et al study reported slightly lower mean age which might be due to the inclusion criteria where the age range was restricted only between 10 and 60 years [10].…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…Yoon et al had all the patients aged 15 years or less [9]. In contrast to this study, Rathi et al study reported slightly lower mean age which might be due to the inclusion criteria where the age range was restricted only between 10 and 60 years [10].…”
Section: Discussioncontrasting
confidence: 57%
“…In our study, discharge was the most common symptom in both the anterior tucking group (96%) and circumferential flap group (86%) followed by hearing loss. It was the same as the study done by Rathi et al [10]. Earache and tinnitus were relatively less common symptoms.…”
Section: Discussionsupporting
confidence: 53%